math

posted by .

3x + 2y + 16x^3z + 6y =

ANSWER: 19x + 8y + 3z

  • math -

    another repeat question, that was answered before

    http://www.jiskha.com/display.cgi?id=1282575195

    You had typed it incorrectly, then corrected it, and now you repeat the incorrect version!

  • math -

    will it did nt help
    cause the answer you give are not in the choices

  • math -

    Kamleen -- you'd save a lot of yours and our time if you also posted the choices!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
  2. Algebra

    There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
  3. Math

    Can you factor these for me? 12x^3 + 6x^2 - 3x - 2 2x^2 +x - 6 25 - 4(x^2 - )^2 y^2 - 3y - 10 (3x - 1)^2 -36 x^3 - 3x^2 - 16x + 48 4x^2 + 7x +3 6x^2 - 19x + 15 5x^4 - 45x^2
  4. math

    3x + 2y + 16x^3z + 6y = ANSWER: 19x + 8y + 3z
  5. math

    3X + 2Y + 16X + 3Z + 6Y = 19x + 8y + 3z
  6. Math

    5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0
  7. Algebra

    Find the product (1 - 3x) (x^2 - 6x - 4)x^2 A. -3x^5 + 19x^4 + 6x^3 - 4x^2 B. -3x^5 - 19x^4 + 6x^3 - 4x^2 C. -3x^5 + 19x^4 - 6x^3 - 4x^2 D.-3x^5 - 19x^4 - 6x^3 - 4x^2
  8. Math

    I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x + 1*** …
  9. Math

    1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x + 8 …
  10. Math

    I need helppp D: ---------------- Simplify the expression -4-5(x+8) *-5x-44 *-5x+36 *-x-8 *-20x+8 5x+6(x-2)-8(x-3) *19x+36 *19x+12 *3x-36 *3x-12 x+8<-28 *x<-36 *x<-20 *x<20 *x<36

More Similar Questions